Analysis of Javanese Mysticism in the Film Qorin Directed by Ginanti Rona - Safitri, Maylina A Girl; Waryanti, Endang; Sasongko, Sempu Dwi (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Horror films have been one of the most popular and influential genres in the film industry since the early 20th century. One of the exciting films studied is Qorin, directed by Ginanti Rona. This film raises a mystical theme about local people's beliefs about supernatural beings. This research uses a theoretical and methodological approach. They were theoretically using Javanese theory studies. The methodological approach uses descriptive qualitative. Primary data related to this research includes images and sentence quotes from the film Qorin. The data source was from the film Qorin on the Bioskop Indonesia Entertainment YouTube channel. The data collection technique for this research is through listening and recording techniques in the film Qorin, directed by Ginanti Rona. Based on the conclusions of this research, it is recommended that 1) Art studies explore more deeply how Javanese mystical values are understood in contemporary films; 2) Literature Learning, providing valuable learning experiences for students in understanding Javanese concepts such as self-introspection and ritual symbolism, this film helps students understand and appreciate cultural values.